Trajectories and determinants of left ventricular ejection fraction after the first myocardial infarction in the current era of primary coronary interventions - Wohlfahrt, Peter; Jenča, Dominik; Melenovský, Vojtěch; Šramko, Marek; Kotrč, Martin; Želízko, Michael; Mrázková, Jolana; Adámková, Věra; Pitha, Jan; Kautzner, Josef (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular ejection fraction (EF) is an independent predictor of adverse outcomes after myocardial infarction (MI). However, current data on trajectories and determinants of EF are scarce. The present study aimed to describe the epidemiology of EF after MI. Methods Data from a single-center prospectively-designed registry of consecutive patients hospitalized at a large tertiary cardiology center were utilized. Results Out of 1,593 patients in the registry, 1,065 were hospitalized for MI type I (65.4% STEMI) and had no previous history of heart failure or MI. At discharge, EF < 40% was present in 238 (22.3%), EF 40–50% in 326 (30.6%) and EF > 50% in 501 (47.0%). Patients with EF < 40% were often those who suffered subacute and anterior STEMI, had higher heart rate at admission and higher maximal troponin level, and had more often HF signs requiring intravenous diuretics. Among subjects with EF < 40%, the follow-up EF was available in 166 (80% of eligible). Systolic function recovered to EF > 50% in 39 (23.1%), slightly improved to EF 40–50% in 44 (26.0%) and remained below 40% in 86 (50.9%). Systolic function improvement to EF > 40% was predicted by lower severity of coronary atherosclerosis, lower leukocyte count, and the absence of atrial fibrillation. Conclusions Despite recent improvements in in-hospital MI care, one in five patients has systolic dysfunction at hospital discharge. Out of these, EF improves in 51%, and full recovery is observed in 23%. The severity of coronary atherosclerosis, inflammatory response to MI, and atrial fibrillation may affect EF recovery.